High-Performance MAPbI3-Based Perovskite Solar Cell: Design, Simulation, and Analysis of Optoelectronic Properties and Efficiency Metrics Using SILVACO TCAD - Rashique Hamjah Chowdhury; Hojaifa Daiyan Chowdhury; Muhammad Johirul Islam; Iqbal Bahar Chowdhury (The Journal of Engineering and Exact Sciences)
In this work, a perovskite solar cell (PSC) based on MAPbI3 has been designed, modeled, implemented, investigated and analyzed in Silvaco TCAD environment. A thin layer of MAPbI3 serves as the photoactive absorber. A thinner layer of PEDOT: PSS based organic material acts as the hole transport layer to enhance the hole transport towards the ITO electrode and a thin layer of ZnO based inorganic material serves as the electron transport layer to assist electron transport to the aluminum electrode. Simulations have been carried out to obtain the energy band diagram and the electric field profile as well as the contour and 2D plots of photon absorption rate, the recombination rate and the photogeneration rate to gain a physical insight of electronic and optical behavior of the proposed solar cell. The current-voltage (JV) characteristics and the external quantum efficiency (EQE) of the device are also plotted. The deduced performance metrics of the proposed PSC demonstrates a short circuit current density (JSC) of 27.247 mA/cm2, an open circuit voltage (VOC) of 0.978 V, a fill factor (FF) of 71.80% and a power conversion efficiency (PCE) of 21.25%, where the EQEs with and without considering the whole device absorption is more than 30% and 50% respectively over the visible and infra-red wavelength range.